Concomitant aortic root and pectus deformity repair in Marfan syndrome patients. (March 2019) - Zakkar, Mustafa; Lansac, Emmanuel; Wurtz, Alain; Brian, Emmanuel
The role of concomitant aortic and pectus repair in Marfan patients remains controversial. We present our surgical technique for concomitant aortic repair of aortic root pathology and pectus correction. The concomitant surgery can be safely achieved in Marfan patients, thus, avoiding the need for a risky second stage operation.